PBG based Terahertz Antenna for Aerospace Applications - Choudhury, Balamati; Danana, Bhavani; Jha, Rakesh Mohan (SpringerBriefs in Computational Electromagnetics, 2016)
This book focuses on high-gain antennas in the terahertz spectrum and their optimization. The terahertz spectrum is an unallocated EM spectrum, which is being explored for a number of applications, especially to meet increasing demands of high data rates for wireless space communications. Space communication systems using the terahertz spectrum can resolve the problems of limited bandwidth of present wireless communications without radio-frequency interference. This book describes design of such high-gain antennas and their performance enhancement using photonic band gap (PBG) substrates. Further, optimization of antenna models using evolutionary algorithm based computational engine has been included. The optimized high-performance compact antenna may be used for various wireless applications, such as inter-orbital communications and on-vehicle satellite communications.